Tonic activation of GABAB receptors via GAT-3 mediated GABA release reduces network activity in the developing somatosensory cortex in GAD67-GFP mice - Ueberbach, Timo; Simacek, Clara A.; Tegeder, Irmgard; Kirischuk, Sergei; Mittmann, Thomas (Frontiers in Synaptic Neuroscience, 2023)
The efficiency of neocortical information processing critically depends on the balance between the glutamatergic (excitatory, E) and GABAergic (inhibitory, I) synaptic transmission. The transient imbalance of the E/I-ratio during early development might lead to neuropsychiatric disorders later in life. The transgenic GAD67-GFP mouse line (KI) was developed to selectively visualize GABAergic interneurons in the CNS. However, haplodeficiency of the GAD67 glutamate decarboxylase enzyme, the main GABA synthetizing enzyme in the brain, temporarily leads to a low GABA level in the developing brain of these animals. However, KI mice did not demonstrate any epileptic activity and only few and mild behavioral deficits. In the present study we investigated how the developing somatosensory cortex of KI-mice compensates the reduced GABA level to prevent brain hyperexcitability. Whole-cell patch clamp recordings from layer 2/3 pyramidal neurons at P14 and at P21 revealed a reduced frequency of miniature inhibitory postsynaptic currents (mIPSCs) in KI mice without any change in amplitude or kinetics. Interestingly, mEPSC frequencies were also decreased, while the E/I-ratio was nevertheless shifted towards excitation. Surprisingly, multielectrode-recordings (MEA) from acute slices revealed a decreased spontaneous neuronal network activity in KI mice compared to wild-type (WT) littermates, pointing to a compensatory mechanism that prevents hyperexcitability. Blockade of GABAB receptors (GABABRs) with CGP55845) strongly increased the frequency of mEPSCs in KI, but failed to affect mIPSCs in any genotype or age. It also induced a membrane depolarization in P14 KI, but not in P21 KI or WT mice. MEA recordings in presence of CGP55845 revealed comparable levels of network activity in both genotypes, indicating that tonically activated GABABRs balance neuronal activity in P14 KI cortex despite the reduced GABA levels. Blockade of GABA transporter 3 (GAT3) reproduced the CGP55845 effects suggesting that tonic activation of GABABRs is mediated by ambient GABA released via GAT3 operating in reverse mode. We conclude that GAT3-mediated GABA release through tonic activation of both pre- and postsynaptic GABABRs restricts neuronal excitability in the developing cortex to compensate for reduced neuronal GABA synthesis. Since GAT3 is predominantly located in astrocytes, neuronal GAD67 haplodeficiency may potentially stimulate astrocytic GABA synthesis through GAD67-independent pathways.